Book Studies And Methods Of Understanding Hadith At The Ddi Mangkoso Islamic Boarding School - Fatmal, Abd. Bashir; Ahmad, Arifuddin; Ahmad, La Ode Ismail (Institut Agama Islam Sumatera Barat Pariaman, 2024)
This research aims to understand the development of hadith studies at DDI Mangkoso Islamic boarding school in Barru Regency from time to time as well as the methods used in studying hadith at the Islamic boarding school. This research uses descriptive qualitative method with socio-historical approach and hadith science. The results of this study indicate that the study of hadith at DDI Mangkoso Islamic Boarding School began when the boarding school was founded by Abdurrahman Ambo Dalle in 1938. This can be seen from the teaching of Ambo Dalle’s book entitled “al-Nukhbah al-Mardiyyah fi al-Hadis al-Nabawiyyah.” Under the leadership of Amberi Said, the study of hadith continued to grow with the introduction of an additional learning system by Faried Wadjedy. Since 1985, under the leadership of Faried Wadjedy, the study of hadith in Mangkoso has flourished with the addition of hadith books, competent and experienced teachers. The method of teaching hadith at the DDI Mangkoso Islamic Boarding School includes two methods: mappangolo kitta’ (sorogan) and ngaji tudang (bandongan), and for the method of reading the book using two methods as well, namely the thematic (maudu’i) method and the khatam kitab method and finally in understanding hadith using two methods as well, namely textual and contextual methods.